Mechanical performance and CO2 uptake of ion-exchanged zeolite A structured by freeze-casting. Issue 9 (September 2015) - Ojuva, Arto; Järveläinen, Matti; Bauer, Marcus; Keskinen, Lassi; Valkonen, Masi; Akhtar, Farid; Levänen, Erkki; Bergström, Lennart
Abstract: Zeolite 4A has been freeze-cast into highly porous monoliths with a cylindrical shape. The brittle monoliths, with lamellar or columnar pores and wall thicknesses between 8 and 35 μm, show a compressive mechanical response along the main pore axis that could be modeled by a buckling behavior. The failure strength is proportional to the density and the amount of transverse bridging across lamella, which was shown to be related to the pore cross-sectional aspect ratio. Monoliths with highly anisotropic pores with a cross-sectional aspect ratio higher than 3 yielded sequentially from the top surface, whereas monoliths with a pore aspect ratio lower than 3 were found to delaminate into longitudinal splinters. The freeze-cast monoliths show a sharp gas breakthrough front with a 1:9 mixture of CO2 and N2, indicating rapid uptake kinetics of the lamellar structures.